2019
DOI: 10.5740/jaoacint.18-0320
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Validation of Qualitative Real-Time PCR Methods for Molecular Diagnostic Identification of Probiotics

Abstract: Backgroud: Probiotics have been shown to benefit human health through several mechanisms, including their role in improving the health of our gastrointestinal tracts. The health benefits of probiotics are strain specific, and therefore it is critical to include the correct strains in probiotic products when claiming specific health benefits. Several studies have reported issues concerning the accuracy of labeling of commercial probiotic products, including inaccurate taxonomy, missing species, or undeclared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 0 publications
1
47
0
2
Order By: Relevance
“…Minimum performance thresholds for all triplex assay calibration were set to R 2 ≥ 0.98 (linearity) and 80–120% efficiency ( Bustin et al, 2009 ). For quantification purposes assay efficiency is recommended to fall within a narrower, 90–110% range ( Broeders et al, 2014 ). Material matrix type and DNA extraction methods can affect the dynamic range; thus, assay performance parameters are evaluated using target DNA extracted using two different methods, from two different matrices, at two different concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimum performance thresholds for all triplex assay calibration were set to R 2 ≥ 0.98 (linearity) and 80–120% efficiency ( Bustin et al, 2009 ). For quantification purposes assay efficiency is recommended to fall within a narrower, 90–110% range ( Broeders et al, 2014 ). Material matrix type and DNA extraction methods can affect the dynamic range; thus, assay performance parameters are evaluated using target DNA extracted using two different methods, from two different matrices, at two different concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…This involves proposed evaluation of applicability, analytical specificity, analytical sensitivity, efficiency, precision, dynamic range, repeatability, and reproducibility ( Newmaster et al, 2019 ). For quantitative assays that are intended to be used for more than detection, other considerations may be required, and acceptable ranges of performance parameters may be tighter, as to ensure sufficient precision ( Broeders et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are living microorganisms that provide health benefits such as improving digestive health and preventing infectious diarrhea, irritable bowel syndrome, and inflammatory bowel disease of hosts (O'Callaghan and van Sinderen, 2016;Floch, 2018;Shehata et al, 2019). Health benefits of probiotics are species-or strain-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, differentiating Bifidobacterium subspecies is necessary. Furthermore, presenting correct species in probiotic products is critical for providing correct information to consumers and claiming health benefits of the product (Shehata et al, 2019). Recently, some studies have shown mislabeling issues such as absence of some species, inaccurate taxonomy information, and undeclared species (Lewis et al, 2016;Morovic et al, 2016) of commercial probiotic products.…”
Section: Introductionmentioning
confidence: 99%